2022
DOI: 10.1186/s43008-022-00098-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomics reveals low levels of inter- and intraspecies diversity in the causal agents of dwarf and common bunt of wheat and hint at conspecificity of Tilletia caries and T. laevis

Abstract: Tilletia caries and T. laevis, which are the causal agents of common bunt, as well as T. controversa, which causes dwarf bunt of wheat, threaten especially organic wheat farming. The three closely related fungal species differ in their teliospore morphology and partially in their physiology and infection biology. The gene content as well as intraspecies variation in these species and the genetic basis of their separation is unknown. We sequenced the genome of four T. caries, five T. controversa, and two T. lae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 167 publications
0
3
0
Order By: Relevance
“…Higher genome sequencing coverage was achieved compared to other genomes available in the public domain. This genome assembly was larger in size, better quality, and more accurate than other available assemblies of T. caries , ranging from 27.14 to 35.80 Mb ( Nguyen et al, 2019 ; Sedaghatjoo et al, 2022 ). Previously, six T. caries genomes were available in the GenBank and NCBI, but these genomes were small in size (USA, Canada) and had a high number of scaffolds (3,606–8,169).…”
Section: Discussionmentioning
confidence: 99%
“…Higher genome sequencing coverage was achieved compared to other genomes available in the public domain. This genome assembly was larger in size, better quality, and more accurate than other available assemblies of T. caries , ranging from 27.14 to 35.80 Mb ( Nguyen et al, 2019 ; Sedaghatjoo et al, 2022 ). Previously, six T. caries genomes were available in the GenBank and NCBI, but these genomes were small in size (USA, Canada) and had a high number of scaffolds (3,606–8,169).…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, several DNA-based methods have attempted to distinguish Tilletia species, but none have been able to separate T. caries and T. laevis ( Mulholland and Mc Ewan, 2000 ; Zouhar et al., 2010 ; Pieczul et al., 2018 ; Forster et al., 2022 ). Phylogenetic studies also failed to distinguish these two species and more recently some authors have suggested that T. caries and T. laevis could be considered as two morphotypes of the same species ( Sedaghatjoo et al., 2021 ; Sedaghatjoo et al., 2022 ; Forster et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…The causal agents of this fungal disease belong to the division of the Basidiomycota and show differences in teliospore morphology. Despite this phenotypic variation, genetic studies suggest that T. tritici and T. laevis might be the same species ( Carris, 2010 ; Sedaghatjoo et al., 2022 ). They also have identical life cycles with teliospores germinating at temperatures between 5°C and 20°C, relatively independent of light conditions ( Lowther, 1950 ).…”
Section: Introductionmentioning
confidence: 99%